A Turn-On Two-Photon Fluorescent Probe for Detecting Lysosomal Hydroxyl Radicals in Living Cells. - Benítez-Martín, Carlos; Guadix-Domínguez, Juan Antonio; Pearson, John; Nájera-Albendín, Francisco; Pérez-Pomares, José María; Perez-Inestrosa, Ezequiel (Elsevier, 2019)
The detection of reactive oxygen species (ROS) in biological systems and its imaging is of great importance. Among them, the hydroxyl radical (radical dotOH) stands out as one of the most reactive, playing an important role in many physiological and pathological processes. Here we report a two-photon (TP) turn-on fluorescent probe with good selectivity and sensitivity towards radical dotOH. The molecular design of this naphthalene-indoline compound enables it to accurately target lysosomes in its non-fluorescent (“off”) state, where interaction with radical dotOH gives rise to the fluorescent (“on”) state and allows for the imaging of radical dotOH generation in living mouse embryonic fibroblast (MEF) cells. The present study provides an approach for improving our understanding of the role of radical dotOH in biological processes.
https://openpolicyfinder.jisc.ac.uk/id/publication/16792
Keywords: Espectroscopia de fluorescencia; Lisosomas; Fluorescent probe; Intracellular radical dotOH detection